Negotiating by the Rules: When Emotional Labor Dictates Emotional Expression in Negotiation - PADDOCK, Elizabeth Layne (Institutional Knowledge at Singapore Management University, 2006)
Participants completed a 20-minute work-related, multi-issue negotiation (Confetti, O'Connor, 1997) in same-sex dyads. Extending negotiation-emotion research (e.g., Barry, 1999), emotional labor (ref. Grandey, 2000) rules were manipulated within the negotiation directions; participants were encouraged to suppress emotions except those expressed and express anger, neutrality, or happiness. Results for attitudinal and behavioral outcomes show three-way interactions among emotional labor rule, negotiator role (manager, employee), and gender. For example, female "managers" achieved more positive outcomes when displaying neutrality than happiness or anger. Men showed the opposite pattern. Emotion regulation techniques (surface acting, deep acting) and experienced emotional intensity also differed across conditions.